Northern India in the Late Nineteenth Century: Quality of Life : Volume I, Part I A to C: 1860s-1870s (Document on Economic History of British Rule in India) - Bagchi, Amiya Kumar,; Bandopadhyay, Arun, (Brill | Manohar Publishers & Distributors, 2020)
This volume is part of the collaborative Project of the Indian Council of Historical Research (ICHR) and Institute of Development Studies Kolkata (IDSK) on the documents pertaining to economic history and quality of life in Northern India in the late nineteenth century. The present volume (divided into three parts A, B, and C) roughly covers the broad period of the 1860s and 1870s. It dwells on documents collected from a wide spectrum of human activity in northern India. They included materials from diverse fields such as agriculture, forestry, population, public health, education, sanitation, and different aspects of the quality of life, in each of which the British Raj was collecting information and directing courses of development in more than one sense. By northern India is meant here what was generally known as the North-Western Provinces (NWP) and the province of Oudh (till 1877, after which it was merged with the NWP) in the late nineteenth century excluding the Punjab. Of the many documents included in the volume, five major issues may be identified: (a) various issues relating to a high land revenue demand and its economic impact (b) education and a few other social issues (c) public health and mortality (d) environmental issues and (e) questions connected with quality of life. Touching on a number of crucial aspects of material conditions and quality of life of people in northern India in the late nineteenth century, the volume stands as a valuable source book for the students of economic history and human development in general.